NMR Structure and IgE Epitopes of Blo t 21, a Major Dust Mite Allergen from Blomia tropicalis - Tan, Kang Wei (American Society for Biochemistry and Molecular Biology, 2020)
JOURNAL OF BIOLOGICAL CHEMISTRY